Indigenous minorities' claims to land - Daniel Weyermann (Intergenerational Justice Review)
Claim of indigenous minorities to land are a significant political issue in many parts of the world. These claims, though, are contested, be it in theoretical, political or legal terms. I consider a position, put forward by Jeremy Waldron, that asserts some theoretical reservations towards indigenous minorities' claims to reparations and land. Waldron seems to assume that indigeneity is no important factor regarding land claims and reparative issues. I propose a rivalling account of indigenous land claims, based on the idea of self-determination. Self-determination itself can be understood in two different ways, it can either be conceived as a form of political autonomy or sovereignty, or it can be understood as having pre-political property rights.